If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5w + 2y)(3w + -3y + -1) = 0 Reorder the terms: (5w + 2y)(-1 + 3w + -3y) = 0 Multiply (5w + 2y) * (-1 + 3w + -3y) (5w * (-1 + 3w + -3y) + 2y * (-1 + 3w + -3y)) = 0 ((-1 * 5w + 3w * 5w + -3y * 5w) + 2y * (-1 + 3w + -3y)) = 0 Reorder the terms: ((-5w + -15wy + 15w2) + 2y * (-1 + 3w + -3y)) = 0 ((-5w + -15wy + 15w2) + 2y * (-1 + 3w + -3y)) = 0 (-5w + -15wy + 15w2 + (-1 * 2y + 3w * 2y + -3y * 2y)) = 0 Reorder the terms: (-5w + -15wy + 15w2 + (6wy + -2y + -6y2)) = 0 (-5w + -15wy + 15w2 + (6wy + -2y + -6y2)) = 0 Reorder the terms: (-5w + -15wy + 6wy + 15w2 + -2y + -6y2) = 0 Combine like terms: -15wy + 6wy = -9wy (-5w + -9wy + 15w2 + -2y + -6y2) = 0 Solving -5w + -9wy + 15w2 + -2y + -6y2 = 0 Solving for variable 'w'. The solution to this equation could not be determined.
| 4X+4*7X^2+2X+5= | | 17x+8=22x-3 | | 2x+5+3x=50 | | 25/n=3/7/30 | | 4*x^2+4*x+1=0 | | 5a^2+11a+2= | | 357*W=998 | | (5/(6-3x))/((10x)/(4-x^2) | | 7x+2x+5=50 | | y-50x+25=0 | | 24x-12-16x=4(2x-4)+4 | | 3t+47=53 | | 4w^2+3w-126=0 | | 3t+47=50 | | -a=8x+3y+18 | | -22+x=x+18 | | 2x^2/x^3 | | 8(a+b)+3(2a+3b)= | | -5y^2-20y+60=0 | | -v^2+6v+16=0 | | 0=1/7 | | (7x-4)(6x+8)= | | U^3/8 | | -7u^2+23u-6=0 | | 0.5=x^3 | | -2v^2-9v-10=0 | | 12-4x/x-3 | | -1/2*7 | | -3=3w+6 | | -s=-4x-8y+17-3x-9y-11 | | 7/2w=28 | | 9x-4(2-2x)=6 |